Determining the relationship between self-directed learning readiness and acceptance of eLearning among culinary students/ Quah Wei Boon, Aznur Fazlin Che Abu Bakar and Norjainah Mohd Yusop - Quah, Wei Boon; Che Abu Bakar, Aznur Fazlin; Mohd Yusop, Norjainah (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
This is a study conducted on Culinary Certificate students of Sungai Petani Community College, Kedah. This study aims to identify the relationship between the level of self-directed learning readiness with the level of acceptance of E-learning among culinary students at KKSP. A total of 106 Culinary Certificate students took part in the study. Descriptive and inferential analysis was used to analyze the data obtained in this study. This study found that the level of acceptance of E-learning among culinary students at KKSP is high. The level of readiness for self-directed learning among culinary students at KKSP is moderate. The Pearson correlation test results showed a significant relationship but a low correlation between the level of acceptance of E-learning and self-directed learning readiness. The majority of respondents accepted the E-learning method in college, and students also have a moderate level of self-directed learning readiness. Suggestions and implication for further study are also recommended.